The Theory of Communicative Action in Da’wah - Iqbal Hussain Alamyar; Umi Halwati (Da'wa Faculty UIN Saizu Purwokerto, 2023)
Abstract This study embarks on an in-depth exploration of the application of Jürgen Habermas’s Theory of Communicative Action in the context of Da’wah. Despite Da’wah’s pivotal role in Islamic societies, there is a conspicuous absence of literature that applies modern communication theories to this practice. This paper aims to fill this gap by scrutinizing how the Theory of Communicative Action, a framework devised for understanding social interactions and communication, can be utilized in Da’wah. The research employs a qualitative approach, with secondary data gathered from a comprehensive review of existing literature on both Da’wah and the Theory of Communicative Action. The findings reveal that the principles of the Theory of Communicative Action can indeed be applied to Da’wah, offering fresh insights into how this religious practice can be understood and executed more effectively in today’s society. Furthermore, this study identifies potential areas for future research, thereby contributing to the ongoing academic discourse on this topic. The implications of this research are substantial, as it not only enriches academic knowledge but also offers practical insights for those engaged in Da’wah. By applying the Theory of Communicative Action more effectively in contemporary society. Keywords: Theory of Communicative Action, Da’wah, Islamic Societies, Social Interactions, Communication theories, Modern Society